Creating leaders for successful change management in Nabila Citra Islamic Kindergarten: Literature Review - Mochamad Irfan; Sanaji Sanaji; Andre Dwijanto Witcaksono; Anang Kistyanto (CV. Ulil Albab Corp, 2024)
The success of change management in an organization is highly dependent on effective leadership. Leaders who are visionary and able to mobilize others are the main keys in navigating transitions and achieving organizational goals. However, creating leaders for successful change management is not easy. Planned and sustainable efforts are needed to build capable leadership capacity and capabilities. This research methodology uses a literature review research method or Systematic Literature Review (SLR), which is a synthesis of literature research carried out by identifying, analyzing, then evaluating through collecting existing data by searching through research selection. Information used by several international journals obtained by screening from Publish or Perish. The results of this research are based on articles in the form of international journals that have international credibility such as Scopus, Web of Science and Pub Med. The benefit of this research is to improve the ability of Nabila Citra Islamic Kindergarten principals and teachers to manage change. The research results show that strong leadership plays an important role in driving the success of change initiatives in kindergarten